Penerapan Model Pembelajaran Inovatif Tipe Talking Stick Dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS Kelas IV SD Negeri Mamajang II Kota Makassar - Sri Hastati (STKIP Andi Matappa Pangkep, 2021)
This study examines social studies learning outcomes through the application of an innovative learning model talking stick type. The main problem of the research is how, through the application of the innovative learning model talking stick type, student learning outcomes towards social studies subjects can increase in grade IV SD Negeri Mamajang II Makassar City. The research objective was to determine the application of the talking stick type of innovative learning model in improving social studies learning outcomes in grade IV SD Negeri Mamajang II Makassar City. This research is a classroom action research using a model developed by Kurt Lewin which includes four steps, namely planning, acting, observing, reflecting. The research subjects were 28 grade IV students. The data collection used test, observation. For the teacher aspect in cycle I, there is still a need for improvement in applying the innovative learning model talking stick type, but in cycle II the application of teacher learning has met the criteria.